Tungsten-Catalyzed Regioselective Allylic Amination - Xu, Wenbin (Synlett, 2024)
A highly regioselective synthesis of allylic amines based on a tungsten-catalyzed allylic amination has been developed. This protocol, which is catalyzed by commercially available W(CO)3(MeCN)3 and 4,4′-di-tert-butyl-2,2′-bipyridine, permits the formation of synthetically useful branched allylic N-aryl- and N-alkylamines in moderate to good yields with a >20:1 branched/linear ratio under mild conditions. The noble-metal-free catalytic system complements conventional allylic aminations catalyzed by an Ir or Rh complex.
Keywords: tungsten catalysis; allylic amines; amination; regioselectivity